THEORETICAL ANALYSIS OF THE SEPARATION OF FINE DIRT FROM COTTON - Ibrokhimova, Dildora; Akhmedov, Kamol; Mirzaumidov, Asilbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article discusses the issue of the distance from cotton to the continuous movement of fine dirt on the surface so that it falls on the tray from the surface of the mesh, that is, the complete separation of impurities from the weight and the angle of inclination affect. Their trajectory according to the law of motion in an inclined plane is determined. The conditions under which the stone will continue to move along the surface of an inclined plane, and small dirt will not hang in the air. Determined the air velocity by associating it with the angle of inclination of the planeConditions are met for the dirt to fall across the surface of the plane through its oblique plane movements, while the fine dirt to continue hanging motion in the air.